Cetyl alcohol and oleic acid sophorolipids exhibit anticancer activity - Dubey, P.; Raina, P.; Prabhune, A.; Kaul-Ghanekar, R. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: Sophorolipids (SLs) are glycolipid biosurfactants that have been shown to have anticancer activity. We investigated the anti-cancer activity of cetyl alcohol sophorolipids (CAS) and oleic acid sophorolipids (OAS) in breast cancer (MCF-7, MDA-MB-231), cervical cancer (SiHa, HeLa) and non-cancerous (HaCaT and RAW264.7) cell lines. Methods: For cell viability assay, MCF-7, MDA-MB-231, SiHa, HeLa, HaCaT and RAW264.7 cell lines were treated with different concentrations (0-160 μg/ml) of OAS and CAS for 24h. The cell viability was determined by MTT dye uptake method. Cell proliferation assay was determined by using trypan blue dye exclusion method. Results: Our preliminary data shows that compared to OAS, CAS exhibited more significant reduction in the viability of MCF-7, MDA-MB-231 and SiHa. However, compared to CAS, OAS induced more decrease in viability in HeLa cells. Interestingly, both the types of SLs did not affect the viability of non-cancerous cells. Moreover, CAS, when used as a coating material, induced proliferation in macrophage cell line, RAW264.7. Conclusion: The present study provides an important clue towards the anti-cancer potential of OAS and CAS derived from Candida bombicola. Interestingly, the ability of CAS to promote the proliferation of non-cancerous cells suggests its future application as a scaffold for enhancing the adhesion and proliferation of normal cells.